Risks for Oculomotor Nerve Palsy and Time to Recovery After Surgical Clipping of Posterior Communicating Artery Aneurysms: A Multicenter Retrospective Cohort Study - da Costa, Marcos Devanir Silva (2023)
BACKGROUND: Aneurysms of the posterior communicating segment of carotid artery (PcomA) have a high risk of rupture; when these nonruptured aneurysms are associated with oculomotor nerve palsy (ONP), the risk of rupture increases compared with asymptomatic nonruptured PcomA. OBJECTIVE: To retrospectively analyze the risk factors involved in ONP secondary to PcomA aneurysm and to study the factors involved in the recovery time of ONP once it is established. METHODS: This was a retrospective study of patients from 10 neurosurgery centers from October 2008 to December 2020. We analyzed age at diagnosis, presence of compressive neuropathy of the oculomotor nerve, presence of aneurysm rupture, largest aneurysm diameter, aneurysm projection, smoking, hypertension, diabetes, time between diagnosis and surgical treatment, as well as the outcome. RESULTS: Approximately 1 in 5 patients (119/511 23.3%) with a PcomA presented with ONP. We found that patients with aneurysms measuring greater than or equal to 7.5 mm were 1.6 times more likely to have ONP than those with aneurysms smaller than 7.5 mm. In our study, the prevalence of smoking in the PcomA + ONP group was 57.76%, and we also found that smokers were 2.51 times more likely to develop ONP. A total of 80.7% showed some degree of improvement, and 45.4% showed complete improvement with a median recovery time of 90 days. CONCLUSION: This study showed that 80.7% of patients with PcomA aneurysms undergoing surgical treatment with aneurysm clipping showed some degree of improvement of the ONP, with a median time to recovery between 90 and 120 days.